Towards a democratic division of labour in Europe? : the combination model as a new integrated approach to professional and family life - Dongen, W. van (Policy Press ; Research Centre of the Flemish Government, 2009)
"Towards a democratic division of labour in Europe? starts from the challenge of balancing these values in all sections of modern society, introducing the Combination Model as a scientific tool for studying the division of professional and family work. Following an integrated conceptual approach, the book explains the historical evolution of the division of labour in modern welfare states. Three policy models are developed to illustrate how a democratic division of labour can be conceived in the long term and the Complete Combination Model is presented as the most suitable for the development of an integrated policy programme." "This book offers inspiration to all scientists, policy makers, representatives of societal organisations and managers who are searching for new theoretical, empirical and policy perspectives."--Jacket